PENINGKATAN STATUS KESEHATAN DI PONDOK PESANTREN DENGAN PENDAMPINGAN TERHADAP KADER KESEHATAN PONDOK PESANTREN AL MUHSIN KOTA METRO - Sri Lestariningsih; Yusro Hadi; Septi Widiyanti; Sadiman Sadiman (JURNAL PENGABDIAN MANDIRI, 2022)
The hostel is a place to live with the students while studying at the Islamic Boarding School. Living together with a number of students in one dormitory will be at risk of contracting various diseases. Transmission occurs when personal and environmental hygiene are not maintained properly. It is very important to know the types of diseases that exist in Islamic boarding schools and the process by which the disease occurs and how the disease spreads to occur as a first step to identify and prevent the occurrence of the disease. Islamic boarding schools are no longer a slum place, but a comfortable place to study and so that people outside the Islamic boarding school are no longer worried about gaining knowledge. The purpose of community service is to provide assistance to Pondok Health Cadres to improve health status at the Al Muhsin Islamic boarding school in Metro City. The implementation method will be carried out by providing health education. Assessment uses a pretest, giving material with lectures, questions and answers and discussions, practice, and posttest. The results show that the knowledge of administrators and teachers about cupping and clean and healthy living behavior before being given counseling and demonstrations has sufficient knowledge with mean value of 63. After being given counseling and demonstrations it can be said to be good because the value of knowledge has increased with mean value of 90.